Several Variables That Affect Financial Performance in Consumer Goods Companies Listed on The Indonesia Stock Exchange in 2021-2023 - Umita Fauziyah; Elly Lestari; Moh. Askiyanto (International Research & Development for Human Beings (IRDH), 2026)
Financial performance demonstrates effectiveness and efficiency in achieving objectives, where good resource management can increase profitability and positive market response. Variations in financial performance in the food and beverage industry on the Indonesia Stock Exchange (IDX) indicate differences in companies' ability to face similar conditions. This study aims to analyze the influence of GCG, which includes the board of directors, audit committee, and institutional ownership, independent board of commissioners, on financial performance in food and beverage sector companies listed on the IDX during the 2021–2023 period. The study population includes all food and beverage companies listed on the IDX, with a purposive sampling technique. From the selection results, 16 companies were obtained as samples, so that using the time series data method, 48 observational data were collected. This study uses secondary data collected through the documentation method. The data analysis technique applied is multiple linear regression. The results of this study reveal that the board of commissioners has a positive and significant influence on financial performance. Meanwhile, managerial ownership shows a negative and significant influence on financial performance. Institutional ownership shows a positive and significant influence on financial performance. Meanwhile, the audit committee has a negative and significant influence on financial performance.